Scientific Mapping of Sharia Accounting Research: A Scientometric Analysis Using VOSviewer on Global Publications (2000-2025) - Judijanto, Loso; Fadlan, Achmad (Westscience Press, 2025)
This study aims to map the global landscape of Sharia accounting research through a scientometric analysis of publications indexed in the Scopus database between 2000 and 2025. Utilizing VOSviewer software, the study visualizes keyword co-occurrence, temporal evolution, author collaboration, and country-level partnerships to uncover core themes, emerging trends, and scholarly networks in the field. The findings reveal that Islamic finance, Islamic banks, sustainability, and corporate social responsibility form the intellectual backbone of the discipline, while newer topics such as financial literacy, religiosity, artificial intelligence, and blockchain represent growing areas of interest. Author co-authorship analysis highlights key contributors and cluster-based knowledge hubs, particularly from Southeast Asia, while country collaboration mapping underscores the dominant roles of Indonesia and Malaysia, alongside increasing contributions from the Middle East, Africa, and parts of Europe. Despite significant progress, the field faces gaps in integrating digital innovations, behavioral insights, and global accounting standards. This study contributes to strategic knowledge development by offering a structured overview of the evolution, maturity, and future directions of Sharia accounting research.